Critical Reflections on the Role of Islamic Early Childhood Educators in Building Tolerance Awareness in Educational Setting - 'Aziz, Hafidh; Aditya Hidayah, Muhamad (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study explores the role of Islamic early childhood educators in fostering tolerance awareness in educational settings while maintaining a strong Islamic identity. It addresses the tension between promoting religious exclusivity and fostering an appreciation for diversity in a pluralistic society, with the aim to contribute to both educational practice and theory on religious tolerance in early education. Design/methods/approach – The study employs a qualitative descriptive exploratory design using content analysis. Data were collected through semi-structured interviews with five teachers and observations of classroom interactions. The diversity management framework was used to analyze the approaches taken by teachers in integrating tolerance education within Islamic curricula. Findings – The research highlights various strategies Islamic educators use to promote tolerance, including storytelling, empathy training, and participatory rule-making. The findings reveal a balance between religious identity and tolerance education, with a sequential approach that prioritizes Islamic principles first, followed by the introduction of tolerance concepts. Despite challenges, such as external influences and technological distractions, the research demonstrates that these strategies positively impact children’s empathy and social behaviors. Research implications/limitations – The study is limited by the sample size and geographic scope, focusing on specific Islamic early childhood institutions. Future research could expand the sample and explore cross-cultural comparisons in different Islamic educational contexts to generalize findings. Practical implications – The findings provide valuable insights for educators, policymakers, and curriculum developers in balancing religious teachings and tolerance education. The study suggests that gradual and integrated approaches to teaching tolerance can foster social harmony and empathy in young children without compromising religious values. Originality/value – This research contributes to the body of knowledge on Islamic education by offering a nuanced understanding of how tolerance can be embedded in early childhood education while maintaining religious integrity. It introduces the concept of sequential tolerance education, which integrates religious principles with empathy and respect for diversity in Islamic settings. Paper type Research paper